Early Cretaceous planktonic foraminifera from the Tethys. The Upper Aptian, planispiral morphotypes with elongate chambers - D. Verga; I. Premoli Silva (Cretaceous Research, 2005)
Early Cretaceous planktonic foraminiferal assemblages include rare planispiral and pseudoplanispiral morphotypes with elongate chambers that BouDagher-Fadel et al. (1997) assigned to Schackoina or accomodated in the new genus Claviblowiella. New findings of well-preserved planktonic foraminiferal faunas from the Lesches en Diois (SE France) section, the Cismon core (NE Italy), the Calabianca (NW Sicily) section and Upper Aptian of Deep Sea Drilling Project (DSDP) Site 545 drilled off Morocco, have allowed a better understanding of the morphological features of these rare, unevenly distributed taxa. Our data demonstrate that each small planispiral species with globular chambers has a correspondent “clavate” morphotype which (as the “normal” forms) exhibit a smooth, finely perforate wall. Consequently, the latter have been here assigned to the genus Globigerinelloides and treated as subspecies of the “non-clavate” taxa. The clavate subspecies belonging to the genus Globigerinelloides here retained are G. duboisi sigali Longoria 1974, G. maridalensis elongatus, new subspecies, G. blowi lobatus, new subspecies and G. paragottisi clavatus new subspecies, while Globigerinelloides minai Obregon de la Parra 1959 is not retained here. In addition, the new genus Pseudoschackoina, type species Planomalina saundersi Bolli 1959 (senior synonym of Hastigerinoides cepedai Obregon de la Parra 1959), has been formalised for individuals possessing elongate, pointed, laterally compressed chambers, bearing tubulospines, arranged on a pseudoplanispiral (dysaxial) coiling mode. Stratigraphically, in the sections studied the first taxon appearing is Pseudoschackoina saundersi, in the uppermost part of the Selli Level (=OAE1a), immediately followed, just above the OAE1a, by all the “clavate” globigerinelloidids. Regarding the last occurrences, Pseudoschackoina saundersi and G. maridalensis elongatus disappear in the lower part of the Globigerinelloides algerianus Zone, Globigerinelloides paragottisi clavatus at the top of the same ...